2009
DOI: 10.1093/brain/awp104
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Alemtuzumab (CAMPATH 1-H) in patients with inclusion-body myositis

Abstract: Sporadic inclusion-body myositis (sIBM) is the most common disabling, adult-onset, inflammatory myopathy histologically characterized by intense inflammation and vacuolar degeneration. In spite of T cell-mediated cytotoxicity and persistent, clonally expanded and antigen-driven endomysial T cells, the disease is resistant to immunotherapies. Alemtuzumab is a humanized monoclonal antibody that causes an immediate depletion or severe reduction of peripheral blood lymphocytes, lasting at least 6 months. We design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
90
1
6

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(100 citation statements)
references
References 26 publications
3
90
1
6
Order By: Relevance
“…These findings indicate that immunosuppression per se is not sufficient to reverse all of the changes in IBM muscle and that the degenerative component of the disease persists even if the inflammation is suppressed. A similar conclusion is suggested by the results of the 2 small trials of T-cell depletion, initially using anti-T-lymphocyte globulin and subsequently alemtuzumab [74,132], which showed a possible slowing in the rate of disease progression, although this needs to be confirmed in larger groups of patients. In the case of the anti-Tlymphocyte globulin trial there was a suggestion that combining T-cell depletion and immunosuppression with methotrexate may be more effective.…”
Section: Immunosuppressive Therapiessupporting
confidence: 62%
See 1 more Smart Citation
“…These findings indicate that immunosuppression per se is not sufficient to reverse all of the changes in IBM muscle and that the degenerative component of the disease persists even if the inflammation is suppressed. A similar conclusion is suggested by the results of the 2 small trials of T-cell depletion, initially using anti-T-lymphocyte globulin and subsequently alemtuzumab [74,132], which showed a possible slowing in the rate of disease progression, although this needs to be confirmed in larger groups of patients. In the case of the anti-Tlymphocyte globulin trial there was a suggestion that combining T-cell depletion and immunosuppression with methotrexate may be more effective.…”
Section: Immunosuppressive Therapiessupporting
confidence: 62%
“…Alemtuzumab, an anti-CD52 antibody that depletes T cells and mature monocytes, has been trialed in IBM but not in PM, DM or NAM [74]. However, there has been a single case report describing the efficacy of alemtuzumab in treatmentresistant PM [75].…”
Section: B-and T-cell Therapiesmentioning
confidence: 99%
“…73 Intravenous immune globulin has been found to be ineffective in controlled trials but may transiently help some patients, especially those with dysphagia. 74,75 Alemtuzumab may provide short-term stabilization, 76 but a controlled study is needed. Treatment with anakinra has also not been successful.…”
Section: Tr E Atment Of Der M At Om Yositis Polym Yositis a Nd Necrmentioning
confidence: 99%
“…There have been continuing attempts to find more effective ways of controlling the immune mediated component of the disease, including T-cell depletion using alemtuzumab (Dalakas et al, 2009) or anti-T-lymphocyte globulin , and therapies specifically targeting inflammatory cytokines such as TNFα with etanercept (Barohn et al, 2006), or IL-1 with anakinra (Kosmidis et al, 2013). Although initial studies have shown that these therapies may have some mild short-term benefits, targeting the immune response alone does not appear to be sufficient to prevent progression of the disease and as yet there are no effective therapies to counter the abnormal protein homeostasis and degenerative aspects of the disease (Breithaupt and Schmidt 2013).…”
Section: Treatmentmentioning
confidence: 99%